2018
DOI: 10.1016/j.ebiom.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Regeneration of Patient-specific Ear-shaped Cartilage and Its First Clinical Application for Auricular Reconstruction

Abstract: Microtia is a congenital external ear malformation that can seriously influence the psychological and physiological well-being of affected children. The successful regeneration of human ear-shaped cartilage using a tissue engineering approach in a nude mouse represents a promising approach for auricular reconstruction. However, owing to technical issues in cell source, shape control, mechanical strength, biosafety, and long-term stability of the regenerated cartilage, human tissue engineered ear-shaped cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
237
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(241 citation statements)
references
References 49 publications
4
237
0
Order By: Relevance
“…PCL can be melted at 60°C and used in a 3D printer, without the need for toxic solvents for dissolution, and extruded in a computer‐controlled pattern to construct structures layer by layer . Moreover, the low melting point of PCL (60°C) allowed a small portion of PGA fibers to fuse themselves into the PCL grids during hot compression molding, making the PCL porous for cell infiltration after PGA degradation, which further facilitates the replacement of the inner core with the patient's own tissue during PCL degradation . In our institute, we are experimenting on the mechanical profile and degradability of the 3D‐printed bio‐scaffold with PCL and cartilaginous cell in vivo and the result of the study about the regeneration of the cartilage from 3D‐printed bio scaffold will be reported shortly.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PCL can be melted at 60°C and used in a 3D printer, without the need for toxic solvents for dissolution, and extruded in a computer‐controlled pattern to construct structures layer by layer . Moreover, the low melting point of PCL (60°C) allowed a small portion of PGA fibers to fuse themselves into the PCL grids during hot compression molding, making the PCL porous for cell infiltration after PGA degradation, which further facilitates the replacement of the inner core with the patient's own tissue during PCL degradation . In our institute, we are experimenting on the mechanical profile and degradability of the 3D‐printed bio‐scaffold with PCL and cartilaginous cell in vivo and the result of the study about the regeneration of the cartilage from 3D‐printed bio scaffold will be reported shortly.…”
Section: Discussionmentioning
confidence: 98%
“…The likely reason for this is that most researchers concentrate on the tissue‐engineering technique without a specific operative plan regarding how to reconstruct ear deformities using the resulting 3D scaffold. Recently, Zhou et al reported the clinical application of 3D‐printed scaffold for auricular reconstruction; however, their scaffold was simply modeled after the natural shape of original ear. They did not consider how to effectively apply the design of the ear scaffold to the actual surgery in ear reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al . reported on the generation of a human ear‐shaped cartilage using 3D printing for patients suffering from microtia, a congenital deformity of the outer ear. After seeding autologous chondrocytes and 3 months of in vitro culture, ear‐shaped cartilage frameworks could be successfully implanted in a total of five patients.…”
Section: Organ and Tissue Biofabrificationmentioning
confidence: 99%
“…For example, 3D printing can be used to fabricate individualized bone prosthetics displaying distinct mechanical properties for superior osteointegration [105,106] as well as cartilaginous structures. Zhou et al [107] reported on the generation of a human earshaped cartilage using 3D printing for patients suffering from microtia, a congenital deformity of the outer ear. After seeding autologous chondrocytes and 3 months of in vitro culture, ear-shaped cartilage frameworks could be successfully implanted in a total of five patients.…”
Section: Three-dimensional (3d) Bioprintingmentioning
confidence: 99%
“…Increasingly intensive research on bioprinting is a response to the high demand for organs in the field of transplantology and is possible due to the continuous development of additive manufacturing technology. The research on this topic concerns both the external structures of the human body, such as ears, skin or nose [11] and internal organs: liver, heart, kidneys [3,7]. The implantology is another area of medicine that uses the 3D printing technology.…”
Section: Introductionmentioning
confidence: 99%